International students as a source of labour supply: Transition to permanent residency - Youjin Choi; Eden Crossman; Feng Hou (Economic and Social Reports)
International students are increasingly viewed as a promising pool of skilled individuals who can be tapped for participation in the Canadian labour market. This is a key motivating factor for providing international students with pathways to obtain permanent residency. This article documents the share of international students who became landed immigrants across various sociodemographic characteristics.